Pengukuran Percepatan Gravitasi Di Kota Metro - Muhammad Barkah Salim; I Wayan Ochha Widiartha; Nyoto Suseno (Jurnal Pendidikan Fisika, 2022)
Metro City is one of the cities in Lampung, Metro City has a height of 30-60 meters above sea level, but the value of the acceleration of gravity in Metro City is not yet known. Therefore, a study was conducted on measuring the acceleration of gravity in Metro City. The purpose of this study is to determine the value of the acceleration of gravity in the city of Metro, and find out how the difference in the acceleration of gravity in the city of Metro is calculated using the mathematical pendulum method and the acceleration of gravity in the CPU-Z application on Android. This study uses quantitative research with experimental methods in which there are numerical calculations and calculation of error/error values. The data collection instrument in this study used an observation sheet and a questionnaire sheet. Data collection was carried out in each sub-district for 5 trials. After that, look for the average size in each sub-district, then do a weighted calculation to find out the magnitude of the acceleration of gravity in the city of Metro. From the results of the study, the magnitude of the acceleration of gravity in Metro City with a mathematical pendulum is 9.86m/s2 with an error value of 0.011m/s2 and with CPU-Z application of 9.800 m/s2 with an error value of 0.003m/s2. The research results are made in the form of modules and validated. The results of the validation stated that it was very feasible with a score of 83.03 %.